IMPLEMENTATION OF THE WEB-BASED ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT APPLICATION IN THE SYMPLE STORE - Aqli Fatona; Havid Syafwan; Akmal Akmal (STMIK Royal, 2024)
Abstract: CRM (Customer Relationship Management) is a type of management regarding the management of the company with customers to improve relationships with customers. CRM can be adapted to E-CRM (Electronic Customer Relationship Management) which requires the role of information technology. Symple Store is a business that sells various t-shirts, apparel, and screen printing services. To see the product, customers must come directly to the store because there is no media to convey product information to customers. Symple Store does not have a way to place an order if the customer does not have the time to come to the store. The purpose of this research is to create a system using E-CRM so that Symple Store sales can be done online and the E-CRM feature is a medium used to maintain the relationship between the store and customers and can also increase customer loyalty. After implementing the E-CRM application on the Symple Store, it can make it easier for customers to place orders online and the E-CRM application becomes a medium for promoting Symple Store products and with E-CRM features such as product information, transactions, discounts, promos, vouchers, chats can maintain the relationship between the store and customers and can also increase customer loyalty. Keywords: e-crm; loyality; symple store. Abstrak: CRM (Customer Relationship Management) merupakan jenis management mengenai pengelolaan perusahaan dengan pelanggan untuk meningkatkan hubungan dengan pelanggan. CRM dapat diadaptasi dengan E-CRM (Electronic Customer Relation Management) yang mana membutuhkan peranan teknologi informasi. Symple Store merupakan usaha yang menjual berbagai barang kaos, pakaian jadi, dan jasa sablon. Untuk melihat produk tersebut pelanggan harus datang langsung ke Toko karena belum adanya media untuk menyampaikan informasi produk kepada pelanggan. Symple Store belum memiliki cara untuk melakukan proses pemesanan apabila pelanggan tidak memiliki waktu untuk datang ke Toko. Tujuan penelitian ini yaitu membuat sistem menggunakan E-CRM sehingga penjualan Symple Store dapat dilakukan secara online dan fitur E-CRM menjadi media yang digunakan untuk mempertahankan hubungan pihak toko dengan pelanggan dan juga dapat meningkatkan loyalitas pelanggan. Setelah menerapkan aplikasi E-CRM pada Toko Symple Store maka dapat mempermudah pelanggan melakukan pemesanan secara online dan aplikasi E-CRM menjadi media promosi produk Symple Store dan dengan adanya fitur E-CRM seperti informasi produk, transaksi, diskon, promo, voucher, chat dapat mempertahankan hubungan pihak toko dengan pelanggan dan juga dapat meningkatkan loyalitas pelanggan.Kata Kunci: e-crm; loyalitas; symple store.